Different biologics for biological-naïve patients with psoriatic arthritis: a systematic review and network meta-analysis - Lin, Jixia; Ren, Yougang (Frontiers in Pharmacology, 2024)
Aim: To systematically compare the efficacy and safety of biologics [tumor necrosis factor inhibitors (TNFi), interleukin (IL) inhibitors, phosphodiesterase-4 inhibitors (PDE4i), and Janus kinase inhibitors (JAKi)] for biological-naïve patients with psoriatic arthritis (PsA).: PubMed, Web of Science, Embase, and Cochrane Library were comprehensively searched until March 12, 2023. Only head-to-head active comparison studies were included, and placebo-controlled studies without active biologic comparators were excluded. Outcomes included musculoskeletal endpoint [American College of Rheumatology (ACR) 20/50/70, resolution of enthesitis, resolution of dactylitis], function endpoint [Health Assessment Questionnaire-Disability Index (HAQ-DI) change, ∆ HAQ-DI ≥ 0.35], composite index endpoint [ACR 50 + PsoriasisArea Severity Index (PASI) 100], and adverse events. Results: Totally 17 studies with head-to-head comparisons of these biologics were included in this systematic review and network meta-analysis. Compared with IL-17A inhibitors (IL-17Ai), TNFi were associated with a lower rate of achieving ACR 20 response [pooled risk ratios (RR)=0.92,95% credibility interval (CrI): 0.86, 0.98].JAKi had the greatest possibility of achieving ACR 20 (50.25%) and ACR 50 (83.03%).The JAKi group had a higher rate of achieving ACR 70 response than the IL-17Ai group (pooled RR=1.25,95%CrI: 1.00,1.57); TNFi were less effective than JAKi in terms of ACR 70 (pooled RR=0.77,95%CrI: 0.64, 0.94). ACR 70 was most likely to be achieved Different biologics for biological-naïve patients with PsA 3 in patients using JAKi (97.48%). The IL-17Ai group had a higher rate of enthesitis resolution than the TNFi group [pooled RR=1.22,95% confidence interval (CI): 1.02,1.47]. Compared with IL-17Ai, TNFi were associated with a lower rate of enthesitis resolution (pooled RR=0.80,95%CrI: 0.72,0.88). Patients receiving IL-17Ai had the highest likelihood of achieving enthesitis resolution (82.76%), dactylitis resolution (58.66%) and the greatest HAQ-DI change (59.74%). IL-17Ai had a similar impact in achieving ∆ HAQ-DI ≥ 0.35 to TNFi (pooled RR=1.15,95%CI: 0.93,1.41). Individuals receiving IL-17Ai had a higher rate of achieving combined ACR 50 and PASI 100 response than those receiving TNFi (pooled RR=1.56,95%CI: 1.29, 1.88). Patients receiving PDE4i were least likely to have adverse events (41.59%).In 2023, considering both efficacy and safety, IL-17Ai may be the better treatment option for biological-naïve patients with PsA requiring biological therapy.